2015
DOI: 10.4102/curationis.v38i2.1517
|View full text |Cite
|
Sign up to set email alerts
|

Clinical learning experiences of male nursing students in a Bachelor of Nursing programme: Strategies to overcome challenges

Abstract: BackgroundMale nursing students are faced with more challenges in the clinical setting than their female counterparts. The ways in which male nurses are viewed and received by nursing staff and patients have an impact on how they perceive themselves and their role in the profession. These perceptions of self have a significant impact on their self-esteem. This study was conducted to explore the clinical learning experiences of male nursing students at a university during their placement in clinical settings in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 19 publications
4
36
1
Order By: Relevance
“…We found that male nursing students who reported more gender barriers perceived a lower nursing image and engaged in fewer caring behaviours than did their less-affected counterparts. Although previous studies found that male students have a positive professional nursing image (Ibrahim et al, 2015), male nursing students still face several gender-barrier challenges (Buthelezi et al, 2015;Juliff et al, 2016), which, in turn, affect students' professional perceptions (Arif & Khokhar, 2016;Buthelezi et al, 2015;Hodges et al, 2017;Ibrahim et al, 2015). The present study contributes to the literature on caring behaviour by showing that genderfriendliness barriers as related to caring behaviour are partially mediated by professional nursing image.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We found that male nursing students who reported more gender barriers perceived a lower nursing image and engaged in fewer caring behaviours than did their less-affected counterparts. Although previous studies found that male students have a positive professional nursing image (Ibrahim et al, 2015), male nursing students still face several gender-barrier challenges (Buthelezi et al, 2015;Juliff et al, 2016), which, in turn, affect students' professional perceptions (Arif & Khokhar, 2016;Buthelezi et al, 2015;Hodges et al, 2017;Ibrahim et al, 2015). The present study contributes to the literature on caring behaviour by showing that genderfriendliness barriers as related to caring behaviour are partially mediated by professional nursing image.…”
Section: Discussionmentioning
confidence: 99%
“…Several researchers have found that male nursing students encounter more challenges in the clinical setting than do female students (Buthelezi et al, 2015;Juliff et al, 2016), particularly because nursing combines professional and feminine values of caring and support (Al-Zein & Al-Khawaldeh, 2015). Further, because there are still a limited number of men in the nursing profession, male nursing students experience isolation and face challenges (Buthelezi et al, 2015). Hodges et al (2017) highlighted some of these challenges, which include a lack of history of men in nursing, a lack of role models, role strain, gender discrimination and isolation.…”
Section: Correlations Among Gender-friendliness Barriers Professiomentioning
confidence: 99%
See 2 more Smart Citations
“…In a qualitative study, male nursing students verbalised that they experienced low self-esteem during nursing practice due to rejection from female patients, and a decreased sense of belonging to a female-dominated profession (5). In certain societies, men who choose a nursing career experience frustration, hopelessness, and confusion about their self-nursing students' perspectives of their internship experiences.…”
Section: Introductionmentioning
confidence: 99%